2022
DOI: 10.1088/1361-6382/ac53b7
|View full text |Cite
|
Sign up to set email alerts
|

Malaise and remedy of binary boson-star initial data

Abstract: Through numerical simulations of boson-star head-on collisions, we explore the quality of binary initial data obtained from the superposition of single-star spacetimes. Our results demonstrate that evolutions starting from a plain superposition of individual boosted boson-star spacetimes are vulnerable to significant unphysical artefacts. For equal-mass binaries, these difficulties can be overcome with a simple modification of the initial data suggested in Ref.[1] for collisions of oscillatons. While we spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 100 publications
2
26
0
Order By: Relevance
“…Individual CO mergers may be distinguished from BBH or BNS mergers through their mass, absence of EM signal, or tidal distortions, impacting the gravitational waveform via the tidal love number [24][25][26][27][28][29][30][31][32][33][34][35]. The latter is a particularly important observation channel for the CO with radii > 50 km considered in this work, although some subtleties may arise in its interpretation [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Individual CO mergers may be distinguished from BBH or BNS mergers through their mass, absence of EM signal, or tidal distortions, impacting the gravitational waveform via the tidal love number [24][25][26][27][28][29][30][31][32][33][34][35]. The latter is a particularly important observation channel for the CO with radii > 50 km considered in this work, although some subtleties may arise in its interpretation [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The smoking gun gravitational wave signals range from slowly decaying oscillations of a BS remnant [125,126] to echos [127,128]. Despite their promise, however, only a handful of necessary numerical simulations of merging BSs and resulting gravitational waveforms exist [129][130][131][132][133][134][135], greatly reducing detectability prospects with matched-filtering techniques. Furthermore, while the dynamical stability and formation of non-spinning stars is wellunderstood [136][137][138][139][140][141][142][143], corresponding studies for rotating stars [144][145][146] revealed only scalar BSs with self-interactions are stable [147,148]; how rotating BSs form dynamically is still an open problem.…”
Section: Boson Starsmentioning
confidence: 99%
“…The data for two single boosted stars are superposed as in Ref. [21] to minimise errors in the Hamiltonian and momentum constraints and spurious oscillations in the scalar field amplitudes of the stars. The physical domain Given that we are dealing with a fully non-linear spacetime in general relativity there is no reason why the naive Newtonian angular momentum should agree so well with the numerically integrated values Q or Q; this could be due to the mass of the stars being M = 0.395(0) m −1 , well below the Kaup limit M Kaup ∼ 0.633 m −1 and the mild boost velocities v = 0.1.…”
Section: Numerical Setup Of Simulationsmentioning
confidence: 99%
“…A charge Q within 3-volume V and a flux F though ∂V , the boundary of V , can be associated with J as described later in Eqs. (20) and (21). If J is conserved then Q is a conserved charge satisfying…”
Section: Introductionmentioning
confidence: 99%